Impact of Climate Change to the Total and Peak Energy Demands of a Northern Finnish Building by 2050 - Jean-Nicolas Louis; Jari Pulkkinen (Zenodo, 2019)
Climate change increases the outdoortemperatures in the future, modifying the energydemand of the buildings from today. As the newbuildings are constructed to last, they should take theimpact of climate change into account during theirdesign phase. The objective of this study is to investigatethe changes in total and peak energy demands inbuildings having different levels of thermal insulation, toexplore if the impacts of climate change are similar to allselected building types by 2050. The impact of climate change to the weather data is gathered from differentclimate change projections to achieve a comprehensiveanalysis of the possible future directions. The newweather files are created using ‘morphing’ method andusing meteorological test reference year for buildingsimulation and measured weather data for constructingthe future weather files. The results indicate that theenergy demand will decrease by 4-8% in passive buildingtype by 2050, with heating demand decreasing 4-10%and by starting to have cooling demand in A1B, A2 andRCP8.5 scenarios for passive building. The scenarios withhigher projections for temperature increase also havelarger decreases in total energy demands indicating thatthe starting of having cooling demand does not overcome the decrease in heating demand. Moreover,the peak demand for heating is projected to decrease inthe future, but at the same time peak cooling demandstarts to occur, which may need to be taken into accountin the future energy system.